The sport development processes in Australia - Sotiriadou, K. (2005)
This thesis is concerned with Australian sport policy, specifically sport development in Australia. Therefore, its theoretical origins lie within the discourse of public policy. While public policy studies are abundant, sport policy research and in particular sport development studies are limited. Hence there is a shortage in the literature on sport development research. Sport nevertheless established itself as a legitimate policy area in Australia in the mid-1970s. Since then, the Federal Government`s involvement with sport policy has expanded and nowadays sport in Australia is very much impacted by Federal Government support. However, increased interest and importance placed on sport have not induced corresponding attention from sport policy studies. This study is a first effort to portray the sport development processes as it occurs in the Australian context. In particular, this thesis examines the impact of the Federal Government involvement with sport policy on the sport development processes at a national level. In doing so, this study explores the roles of the key sport development players and the ways sport policies shape sport development processes. Additionally, the study explores the available sport development pathways and the relationships between sport policy players, policies and sport development processes. There have been previous efforts to depict the processes involved with sport development by means of a pyramid that incorporates mass participants at its base and the elite athletes at its peak. This framework provides a very simplistic representation of sport development and does not explicate the embedded processes (Eady, 1993, Shilbury & Deane, 2001). The aforementioned inadequacy of the existing framework to explain sport development led to grounded theory research. Grounded theory is a qualitative research approach formulated by Glaser and Strauss (1967) as a means of generating theory, when existing theoretical frameworks are inadequate to explain a phenomenon, which is embedded in systematically gathered and analysed data (Glaser & Strauss, 1967; Bryman, 1988). Strauss and Corbin (1994) argued that if the research question concerns a process, the method of choice for addressing the question is grounded theory. This method led to the constant comparison and coding of data from the Annual Reports of 35 National Sporting Organisations in Australia. These documents covered the years from 1999-2002 (inclusive) and are linked to a Federal Government funding cycle. Grounded theory research is viewed as 'the foundation for subsequent deductive studies that test out the resulting theory or interventions based on it' (Oshansky, 1996, p. 394). Hence, the model this thesis offers is subject to further empirical testing and future research. The results of the study provide a theoretical framework to understand the Sport Development Processes in Australia. The Sport Development Processes framework illustrates that at the hub of successful sport development there are three major and interrelated requirements: a) Stakeholders, b) Practices and c) Pathways. Sport Development Stakeholders (i.e. governments, sporting organisations and significant others) provide the unity and teamwork necessary for the Sport Development Practices that in turn provide the required Sport Development Pathways. These pathways as the result of sport stakeholder involvement and policy implementation allow Sport Development Processes to occur. According to the Sport Development Processes framework there are three interrelated processes (i.e. Attraction, Retention/Transition, and Nurturing) which involve attracting, retaining and developing the most skilled athletes, building participation and using sport performance to positively influence community involvement with sport. For each process to be successful, a different combination of stakeholder involvement and practices (hence resulting pathways) is necessary. This model provides a unique contribution to the field of sport policy, as it is the first theoretical attempt to fill the void regarding sport development processes. In the process, sport development officers, policy makers and sporting organisations at all levels around Australia are provided with a comprehensive model that assists and advances understanding of sport development processes.